Efektivitas Strategi komunikasi Komunitas Hijabers Semarang Terhadap Sikap Mahasiswi Fisip Undip Untuk Menggunakan Jilbab - Rizka Devi Kusumawardhani (Interaksi, 2012)
Today many emerging communities - communities of headscarves in Indonesia, including in thecity of Semarang. The community came from a group of veiled women who have a movementthat took its people, especially Muslim women not wear veils to wear veils. This community wasnamed Community Hijabers Semarang. Establish a community vision is a community that willaccommodate activities associated with the veil and Muslim women. From fashion, hijab styleand everything that would make the Muslim a better. And it is hoped through this community,every Muslim can meet new friends, get to know each other and learn from one another.Theory used in this study using the Theory of Persuasion and social influence, which explainshow the effort made to persuade the audience to learn a new information, changing emotions,and to act in such a way. This study used a questionnaire as an instrument of data collection andstudy of literature to obtain additional information related to this research. Target population isstudents Fisip Undip and sampled proportionally as much as 78 random sampling of respondents.The analysis used is a simple linear regression analysts.This study found that there is a relationship between communication strategy CommunityHijabers student attitudes to wear veils. The more effective communication strategy undertakenHijabers Community will increasingly affect the attitude of students to wear veils. Based on thecalculation of statistical tests conducted found the coefficients, the greater the value ofsignificance is 0.000 with a correlation constant of 0.628 and 18.578 states that if no variable Xthen the variable Y is 18.578. Regression coefficient of 0.421 X variable Y variable will increaseby 0.421. Ketetentuan accepted or rejected the hypothesis testing is to see the significance. sothat it can be said of variables influence the effectiveness of communication strategies on studentattitudes (Y) is significant at the 95% confidence level. Figures adjusted R Squere is 0.394means 39.4% in student attitudes can be explained by variebel effectiveness of communicationstrategies. So it can be concluded if the student Fisip Undip require a more attractive strategy inevery activity undertaken Hijabers Community Semarang.